2009
DOI: 10.3413/nukmed-0189
|View full text |Cite
|
Sign up to set email alerts
|

Value of diagnostic radioiodine scintigraphy and thyroglobulin measurements after rhTSH injection

Abstract: SummaryMeasurements of thyroglobulin (Tg) levels 72 h after administration of recombinant human thyrotropin (rhTSH) are recommended by the manufacturer in the follow-up of patients with differentiated thyroid carcinoma (DTC). In our department, Tg measurements are performed both 24 h and 72 h after administration of rhTSH, together with 72 h post rhTSH 131I whole body scintigraphy (WBS). The objective of this study is to compare the diagnostic usefulness of Tg measurements 24 and 72 h after rhTSH administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Only the study by Verburg et al analyzed high-risk patients separately, but the high-risk group contained only 44 patients and lacked a clear formulation of high-risk criteria. Still, the authors concluded that routine DxWBS might be omitted in high-risk patients just as in low-risk patients (12). Other studies have found that in their study population, which also included high-risk patients, DxWBS had no value additional to that provided by stimulated thyroglobulin measurement (12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Only the study by Verburg et al analyzed high-risk patients separately, but the high-risk group contained only 44 patients and lacked a clear formulation of high-risk criteria. Still, the authors concluded that routine DxWBS might be omitted in high-risk patients just as in low-risk patients (12). Other studies have found that in their study population, which also included high-risk patients, DxWBS had no value additional to that provided by stimulated thyroglobulin measurement (12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…However, the original phase III clinical trial comparing rhTSH and THW preparation for DxWBS concluded that rhTSH DxWBS was less sensitive than DxWBS using THW (7). In this phase III trial, rhTSH DxWBS was inferior to THW DxWBS in 18 (29%) of 62 patients and failed to detect metastatic disease in 8 (13%) of 62 patients with positive scans.…”
mentioning
confidence: 88%
“…Several studies analyzed the additional value of DxWBS, but also in low-risk patients (3)(4)(5)(6)(7)(8)(9)(10). Most studies found no additional value of DxWBS in their patient group (3-9).…”
Section: Replymentioning
confidence: 99%
“…Several studies analyzed the additional value of DxWBS, but also in low-risk patients (3)(4)(5)(6)(7)(8)(9)(10). Most studies found no additional value of DxWBS in their patient group (3)(4)(5)(6)(7)(8)(9).…”
Section: Replymentioning
confidence: 99%